1989
DOI: 10.1357/002224089785076163
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of wind forcing of eddies and jets in the California Current System

Abstract: A high-resolution, multi-level, primitive equation ocean model is used to examine the response to wind forcing of an idealized flat-bottomed oceanic regime along an eastern ocean boundary. A band of steady alongshore, upwelling favorable winds, either with or without alongshore variability, is used as forcing on both anf-plane and a ,a-plane. In each experiment a wind-driven equatorward coastal jet and a poleward undercurrent are generated. In time the coastal jet and undercurrent become unstable and lead to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…The generation of a poleward undercurrent along the west coast is consistent with previous process-oriented modeling studies which have shown that a poleward undercurrent can be generated due to meridional variability in the predominantly equatorward wind stress (Batteen et al, 1989) and/or to the planetary beta effect (e.g., McCreary et al, 1986;Batteen, 1997). The beta effect allows the existence of freely propagating planetary waves, i.e., Rossby waves (Gill, 1982).…”
Section: Wind Forcing Over a Flat Bottomsupporting
confidence: 88%
“…The generation of a poleward undercurrent along the west coast is consistent with previous process-oriented modeling studies which have shown that a poleward undercurrent can be generated due to meridional variability in the predominantly equatorward wind stress (Batteen et al, 1989) and/or to the planetary beta effect (e.g., McCreary et al, 1986;Batteen, 1997). The beta effect allows the existence of freely propagating planetary waves, i.e., Rossby waves (Gill, 1982).…”
Section: Wind Forcing Over a Flat Bottomsupporting
confidence: 88%
“…2.0;10 cm s\) as in Batteen et al (1989). Holland (1978) showed that the highly scale-selective biharmonic diffusion acts predominantly on submesoscales, while Holland and Batteen (1986) found that baroclinic mesoscale processes can be damped by Laplacian lateral heat diffusion.…”
Section: Model Equationsmentioning
confidence: 92%
“…The numerical model in this study was originally used for a coarse resolution, closed basin by Haney (1974), and later adapted for eddy-resolving, limited EBC regions with open borders on the northern, western, and southern boundaries by Batteen et al (1989), Batteen (1997), and Batteen and Butler (1998). The limited area EBC model is multi-level, uses non-adiabatic primitive equations on a beta-plane, and has both baroclinic and barotropic velocity components.…”
Section: Model Equationsmentioning
confidence: 99%
See 2 more Smart Citations